Digital teaching portfolios: Catalysts for fostering authentic professional development - Natalie B. Milman; Clare R. Kilbane (The Canadian Network for Innovation in Education (CNIE), 2005)
This paper reports the findings of a qualitative study examining the role of digital teaching portfolios in teachers' professional development and classroom practice. The participants, all teachers, took part in a formal course in which they develop a digital teaching portfolio. The findings suggest that the processes involved in creating digital teaching portfolios fostered their authentic professional development, and were a catalyst for their ongoing professional development. Furthermore, engagement in creating a portfolio was instrumental in these teachers' self-discovery and learning.